A five-year survey of ocular shotgun injuries in Ireland. Issue 6 (June 1987) - Roden, D; Cleary, P; Eustace, P
Abstract : Between November 1980 and September 1985 20 patients in Ireland sustained accidental ocular shotgun injuries severe enough to necessitate hospital admission. Eight patients had contusion injuries and 12 perforating injuries. Contusion damage was disproportionate to the size of the pellet. Through and through perforation of the globe occurred in eight patients; the remaining four patients in this group had retained intraocular pellets. Twelve patients sustained perforating eye injuries. Those that were treated by primary closure alone lost the sight in that eye. Those treated by vitreoretinal surgery recovered vision directly related to where the pellet had its exit from the eye. It was possible to contact 15 of the patients. All 15 were shooting pheasant. It was not possible to relate the distance of the patient from the gun to the severity of the ocular injury.